2010
DOI: 10.1590/s0101-28002010000200005
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre a depuração plasmática de creatinina utilizando urina coletada durante 24 horas e 12 horas

Abstract: Introduction: Creatinine concentration in plasma has been used to evaluate renal function. However, the endogenous creatinine clearance (CrCl) is more sensitive to this goal. Objective: Correlate the CrCl calculated from urinary collects of 12 h and 24 h. Methods: Ninety five volunteers (34-64 y) collected the urine for 24 h into two bottles: night, from 7 am to 7 pm and day, from 6 am to 7 pm. A fasting blood sample was used to measure plasma creatinine. Correlation between variables was determined by Pearson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
2
5
0
1
Order By: Relevance
“…This is slightly softened by using the CG-corrected formula for the body surface. Sodré et al (2007) reported a good correlation between kidney function and the results of the CG formula; however, Silva et al (2010) found a moderate coefficient of correlation between the GFR measured by collecting urine for 24 h and the GFR calculated by the CG formula, which is similar to the results of the present study, in which the CG formula exhibited a lower correlation and agreement with creatinine clearance than all of the other formulae.…”
Section: Discussionsupporting
confidence: 86%
“…This is slightly softened by using the CG-corrected formula for the body surface. Sodré et al (2007) reported a good correlation between kidney function and the results of the CG formula; however, Silva et al (2010) found a moderate coefficient of correlation between the GFR measured by collecting urine for 24 h and the GFR calculated by the CG formula, which is similar to the results of the present study, in which the CG formula exhibited a lower correlation and agreement with creatinine clearance than all of the other formulae.…”
Section: Discussionsupporting
confidence: 86%
“…ClCr is widely used as a measure of renal function in clinical practice, but it tends to overestimate GFR 8 , 14 , mainly due to the proximal tubular secretion of 10% to 40% of urinary creatinine. Another relevant problem with ClCr is the high probability of error in urine collection within 24 hours 14 , despite the lack of quantitative data in the literature 15 - 17 . Our study found that 46% of the measurements had inadequate urine collection.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of creatinine clearance (Cl cr ) is challenging to carry out due to difficulties with 24‐h urine collections 40 . Some studies have suggested that shorter collecting times, like 12‐ and 2‐h urine collections, may be comparable to 24‐h Cl cr measurements 41,42 . Other variables, such as diet, exercise, and disease conditions, can affect creatinine production, which confounds our interpretation of Cl cr .…”
Section: Estimated Kidney Function Equations In Older Adultsmentioning
confidence: 99%